Future Banking: Which measure can stand the test of time? An evaluation of two contrasting strategies - Kam, Chun Hoe (2014)
Rising regulatory charges, increasingly sophisticated clientele and highly volatile market are some of the main concerns dominating the minds of most bank executives of late. Barely just recovered from one of the worst financial turmoil to date, the last thing to expect is the introduction of new regulatory restrictions such as Basel III and Volcker Rule that further restrict the means for banks to generate additional returns. As margins start to shrink, thanks to the increase in financial literacy of the society, financial institutions start to venture into other means to maintain their positive returns. Two rather contrasting approach have been noticeable of late possibly due to the culture and regulatory background that shape the modus operandi of these organizations. Financial institutions in the Western hemisphere have opt for the use of capital equipment such as trading platforms and other e-banking means to capitalize on their already established branch network and possibly eliminate any operational slack in the process. Meanwhile banks in the Eastern of the globe may have a different take, as they went on a prowl acquiring stakes and assets from their once stronger peers possibly in a bid to establish a presence in the global market scene and not to mention take advantage of the region’s trade dynamics. This research paper begin with an examination of the regulatory background that possibly shape the strategies of these financial institutions before conducting a qualitative and quantitative evaluation of both measures with the objective of which measure could stand the test of time moving forward. Results are not that clear cut but nonetheless, it is possible that some thoughts may have been provoked in the quest to identify a strategy that best able to navigate financial institutions through the most challenging decade yet that is soon to come.